Numerical Investigation for the Distribution of Air Velocity and Temperature in an Occupied Zone by using Displacement Ventilation - Dr.Israa Ali Abdulghafor (Genius Journals, 2022)
The current investigation presents a numerical analysis to distribute the temperatures and velocities in an occupied zone under different provided air temperatures and velocities. The steady-state and incompressible flow conditions are assumed by CFD simulation. The provided air velocities are investigated of (0.75,1,1.25and1.45)m/s with 1600 was a fixed internal load and a fixed provided air temperature of 18 °C. The provided air temperatures are investigated at (18,20,22 and 24) °C with 1600W as a fixed internal load and fixed provided -air velocity of 0.75m/s. The results show the best velocities and temperatures distribution at the provided -air velocity of 0.75m/s and air temperature of 18°C. While best rate air temperature for an occupied zone is achieved at provided-air velocity and temperature of (1.45m\s and 18 °C) respectively. The air distribution becomes more turbulence as provided air velocity and temperature increase
Keywords: Numerical investigation; Displacement ventilation; Tempertaure Disrbution; Fluent 14.5